Discovering Empathy: A Labovian Analysis of Gus Worland’s Personal Story in TEDx Talk - Ellysa Rahmani Putri Astuti (STAIRS: English Language Education Journal, 2025)
This study discusses how attitude can evoke empathy and emotional engagement in narrative. The personal story of Gus Worland was analyzed in his TEDx Talk using the Appraisal Theory framework, particularly the subsystem of attitude, including affect, judgment, and appreciation, to assess emotional expressions, behavioral assessments, and evaluative stances. It also uses Labov's framework of narrative analysis to show how structural elements like evaluation contribute to the resonance of empathy in the audience. Qualitative research design, therefore, has been used to analyze the transcript of the TEDx Talk by Worland through content analysis. The results show that the effect amplifies emotional resonance, judgment deepens moral engagement, and appreciation highlights the transformative value of connection. Labov's six narrative components further elaborate coherence and impact; the sections of evaluation and resolution foster a reflective and actionable response among audiences. The study contributes to the knowledge of empathy-building for public speakers and mental health advocates on ways to employ narrative strategies for impactful communication. It will be useful for other researchers to extend this framework across various advocacy contexts to gain a deeper understanding of narrative empathy in its universality.